Tersilochinae (Hymenoptera: Ichneumonidae) of Japan : two new species, a new combination and 23 new country records - Khalaim, Andrey I. (Zootaxa, 2022)
Based on a large amount of material from Japan, two species, Allophroides watanabei sp. nov. and Tersilochus (Tersilochus) serratoides sp. nov., are described as new to science, one new combination, Probles (Euporizon) ecarinata (Khalaim, 2005), comb. nov., is proposed, and following new country records are provided: genus Allophroides Horstmann, Diaparsis (Diaparsis) egregia Khalaim, D. (Nanodiaparsis) ussuriensis Khalaim, Gelanes dentator Khalaim & Lee, G. provectus Balueva & Lee, G. simillimus Horstmann, Phradis gibbus (Holmgren), Ph. vespertinus Khalaim, Probles (Euporizon) carinator Khalaim, Pr. (E.) ecarinata (Khalaim), Pr. (E.) fulgida Khalaim & Balueva, Pr. (E.) hankaensis Khalaim, Pr. (E.) korusa Khalaim & Kim, Pr. (Microdiaparsis) caudiculata Khalaim, Pr. (M.) neoversuta (Horstmann), Pr. (Rugodiaparsis) ruficornis (Szépligeti), Tersilochus (Tersilochus) curvator Horstmann, T. (T.) gangwonus Khalaim & Lee, T. (T.) grandiculus Khalaim, T. (T.) impunctator Khalaim, T. (T.) juxtus Khalaim and T. (T.) liopleuris (Thomson). The number of known Japanese species of Tersilochinae is raised from 25 to 48, or almost double.                Also, Probles (Euporizon) interruptor Khalaim & Lee, Tersilochus (Tersilochus) fidicinus Khalaim & Lee, and T. (T.) gangwonus Khalaim & Lee, are recorded for the first time from Russia. Males of Phradis hikosanus Khalaim and T. (T.) fidicinus Khalaim & Lee are described for the first time. Brief annotations to all occurring in Japan genera, and diagnoses, remarks on taxonomy and colour illustrations to Japanese species, are given.